Emigration from the perspective of Polish health professionals – insights from a qualitative study - Domagała, Alicja; Kulbat, Aleksandra; Parzonka, Kamila (Frontiers in Public Health, 2022)
The Polish health workforce is facing many problems, including shortages, heavy workload, burnout, and dissatisfaction, which may lead to job emigration, mainly among younger generations. The objective of the article is to explore the reasons, consequences, and circumstances of the emigration of Polish health professionals with a qualitative approach. We have conducted semi-structured interviews with 15 practicing health professionals, exploring the perspectives of different professions and different generations. The interviews were conducted using the on-line MS Teams platform from February until March 2022. We transcribed all interviews verbatim and performed directed qualitative content analysis. Currently, the scale of emigration is rather stable and mainly affects the younger generations. The main reasons for emigration, as indicated by representatives of different health professions, are similar, including excessive workload and long working hours. However, doctors and dentists also emphasized problems with professional development and specialization training, while nurses, midwives, and physiotherapists underlined problems with low prestige and work autonomy. Taking into account the substantial shortage of health workforce and the high average age of practicing health professionals, emigration requires special attention from health decision-makers. Implementation of an effective mechanism for monitoring the emigration of medical staff is recommended.